Primary retroperitoneal mucinous cystadenoma in a male patient: a case report - Yau, Joachim Wen Kien; Tan, Cher Heng; Chau, Cora Yuk Ping; Wong, Kar Yong (International Surgery Journal, 2019)
Primary retroperitoneal mucinous cystic neoplasms are very rare, especially in men. To our knowledge, only 13 cases of such neoplasms have been reported in men to date. The most common type is the primary retroperitoneal mucinous cystadenoma, which almost invariably affects females. Most patients present with non-specific symptoms. In this case report, we will describe a case of a 53 year old male patient who presented with raised CEA tumour marker and vague right sided abdominal discomfort. A computed tomography (CT) scan was performed, which revealed a 4.9 × 4.7 × 7.5 cm lobulated retroperitoneal cystic lesion abutting the posterior wall of the mid ascending colon. A laparoscopic excision was eventually performed with complete removal of the retroperitoneal cystic lesion. Subsequent histological assessment confirmed the diagnosis of a primary retroperitoneal mucinous cystadenoma with borderline malignancy. On comparison with a prior CT scan performed about seven and a half years earlier, we managed to derive a doubling time of about 626 days, which is the first reported case in English literature to document the growth rate of such a tumour. The patient has since been discharged well, with no evidence of tumour recurrence on an interval CT scan.